2016
DOI: 10.14393/bj-v32n5a2016-33068
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizers with coated urea in upland rice production and nitrogen apparent recovery

Abstract: Urea is the most used N fertilizer for upland rice, however, a great percentage of N loss can occur with the use of this fertilizer. The use of products that provide reduction of N loss for urea fertilizers can contribute to increase N use efficiency. The objective of this study was to determine the effect of N rates applied in the form of coated urea in the content and accumulation of N in dry biomass, apparent recovery of nitrogen and grain yield of upland rice. The experimental design was a randomized compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This fact shows that for the conditions tested, coated urea sources behave similarly to urea. Similar results were obtained by Bernardes et al (2015) and Silva Junior et al (2020) with beans, by Carvalho et al (2016) and Fageria and Carvalho (2014) with rice, by Prando et al (2013) with wheat, and by Silva et al (2012) with corn. Thus, it appears that under the conditions of this study, the modifications made to urea aiming to increase its efficiency were not effective in providing higher yields of corn and common bean grains in the two years evaluated, since urea provided results that were similar to those provided by other sources.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This fact shows that for the conditions tested, coated urea sources behave similarly to urea. Similar results were obtained by Bernardes et al (2015) and Silva Junior et al (2020) with beans, by Carvalho et al (2016) and Fageria and Carvalho (2014) with rice, by Prando et al (2013) with wheat, and by Silva et al (2012) with corn. Thus, it appears that under the conditions of this study, the modifications made to urea aiming to increase its efficiency were not effective in providing higher yields of corn and common bean grains in the two years evaluated, since urea provided results that were similar to those provided by other sources.…”
Section: Discussionsupporting
confidence: 82%
“…The use of nitrogen provided significant increases in corn and common bean yields. Likewise, Fageria (2014), Carvalho et al (2016) also reported an increase in the grain yield of agricultural crops with the use of N in Brazilian Latosols. Nitrogen is an important nutrient in crop development, and the use of nitrogen fertilizers in crops is directly related to increased yield (FAGERIA, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…All treatments led similar grain yields, so the stabilized fertilizers provided no advantage over urea in this respect. Carvalho et al (2016) assessed N topdressing with urea in relation to fertilizers such as urea + NBPT, zeolite-coated urea and urea coated with Cu and B applied to aerobic rice and obtained similar results.…”
Section: Rice Yield and Nitrogen Use E Ciencymentioning
confidence: 80%
“…However, some authors have found exponential increases in N 2 O emissions depending on the N fertilizer rate used (Shcherback et al, 2014). Nitrogen fertilizer management and starting ooding up to 3 days after N application is the ideal combination to maximize nitrogen use e ciency while minimizing N losses (SOSBAI, 2014; Carvalho et al, 2016). This can explain the similarity of seasonal N 2 O emissions among fertilizers in GS2, when all SNF performed similarly to common urea.…”
Section: N 2 O and Ch 4 Emissionsmentioning
confidence: 99%